Science and communication : a critical analysis of the coverage by the Namibian press of the introduction of communal conservancies as a form of community based natural resource management (CBNRM) - Barnard, Margaretha Magdalena (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2004.